Sharing economy services in Dhaka: A change towards women's perception of commuting - Md. Mukitul Hoque; Bildana Haque Saumi (Rajagiri Management Journal (RAMJ), 2022)
Purpose - In the modern era of transportation, using a ride-sharing service can add an extra value to the lifestyles of women. Also, women are thinking about the ride-sharing service, what are the factors they consider while purchasing the service and so on. The purpose of this study is to find out women's perception of ride-sharing services. Design/methodology/approach - This paper is based on deductive research approach and descriptive research design. This paper has followed mixed research method by using qualitative and quantitative data. By dividing the larger population into subgroups, the researchers have conducted a survey on 240 respondents. To select these respondents, researchers have applied simple random technique. Based on a survey on consumers' buying behaviour of ride-sharing service, the researchers tested the impact of tangibility, reliability, safety, fare, efficiency and convenience as the factors for choosing ride-share rather than other public transportation. Findings - The study results indicate that reliability which includes consistency, punctuality and schedule routes are the major concerning issue for women while choosing ride-share service. Women are also concerned about efficiency which includes global positioning system tracking, smartphone technology and so on. One of the important criteria for choosing a ride-sharing service is safety, which includes verified drivers, and drivers review scores. So, reliability, efficiency and safety are the most effective issues. On the other hand, tangibility, fare and convenience do not affect that much. Originality/value - To the best of the authors' knowledge, this is the first research to scrutinize the sharing economy service in Dhaka city towards women's perception of commuting.
Keywords: 650; GPS tracking; Ride-share; Sharing economy; Smartphone technology